FEASIBILITY AND COMPARATIVE ANALYSIS OF SOLAR POWER TUBE WELL WITH EXISTING CONVENTIONAL SYSTEMS AND ITS UTILIZATION IN IRRIGATION OF THE AGRICULTURAL LANDS. - Muhammad Dawood Bukhari; Hassan Farid Khan; Muhammad Saqib Hameed; Muhammad Yasir; Muhammad Safdar; Usman Ahmad; Waqas Aleem Khawaja (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Solar energy plays an essential role in creation of the electricity in all the fields of life. Now a day with the increased demand and high prices of the electricity production, it is not feasible to run all the electrical equipment on the electricity being supplied by the local authorities. In this research paper a comprehensive study based on the feasibility of the solar energy for the tube well has been conducted in district Bhakkar, Punjab. The tube well discharge was 25mm3/sec having a total hydraulic head of 25m. The borehole depth under the earth is 110 ft (50 ft blind + 60 ft screen) using borehole diameter of 12.7cm (5 in). A three-stage submersible pump of 15.24cm (6 in) diameter was laid in borehole to a depth of 65 ft. The submersible pump get power from 24 solar panels of having a magnitude of 360 watts each. In wintry weather the discharge of solar operated powered tube well varies from 5.00 to 24.00 mm3/sec and in summer it ranged from 12.00 to 25.00 mm3/sec. The peak discharge of the solar tube well properly changed into as 5 to 6 hrs/day in winter and summer time, respectively. The sugar cane crop was planted and irrigated with water pumped from a tube well that was operated by consuming solar energy and the production capacity of the tubewell is about 95 tons/hectare in a year. The cost volume profit analysis of a properly powered solar tube well vs a diesel-operated tube well nicely confirmed that the capital recovery period of solar powered tube well would be 1.42 years of its 10 years of usable life with a 36% internal rate of return (IRR). At discount rates of 2, 4, 6, and 8%, the solar powered tube well’s BCR (Benefit Cost Ratio) was 1.5, 1.42, 1.38, 1.62 respectively. At discount factor of 2, 4, 6, and 8%, the solar-powered tube well’s NPV (Net Present Value) was 0.91, 0.87, 0.84, 0.75 million rupees, respectively. The Results indicated that the solar tube well is a sensible desire and need of the modern time due to its quick payback length.